2019
DOI: 10.1080/03007995.2019.1585064
|View full text |Cite
|
Sign up to set email alerts
|

Predicting risk for radiographic damage in rheumatoid arthritis: comparative analysis of the multi-biomarker disease activity score and conventional measures of disease activity in multiple studies

Abstract: Objective: To compare the multi-biomarker disease activity (MBDA) score with the DAS28-CRP and CRP for predicting risk of radiographic progression in patients with rheumatoid arthritis. Methods: Published studies of the MBDA score and radiographic progression with 100 patients per cohort were evaluated. Rates of radiographic progression over 1 year were determined across the low/moderate/high categories for MBDA score (low/moderate/high: <30, 30-44, >44), DAS28-CRP (low/ moderate/high: 2.67, >2.67-4.09, >4.09)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 34 publications
(117 reference statements)
4
22
0
Order By: Relevance
“…Prior studies have reported that baseline MBDA score can predict risk for radiographic progression [11,[32][33][34], and that the MBDA score is a better predictor of radiographic progression than conventional measures of RA disease activity [33,35]. A study of patients with early RA found that lower MBDA scores in patients with inadequate clinical response to methotrexate monotherapy were associated with better clinical responses to subsequent triple therapy [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have reported that baseline MBDA score can predict risk for radiographic progression [11,[32][33][34], and that the MBDA score is a better predictor of radiographic progression than conventional measures of RA disease activity [33,35]. A study of patients with early RA found that lower MBDA scores in patients with inadequate clinical response to methotrexate monotherapy were associated with better clinical responses to subsequent triple therapy [36].…”
Section: Discussionmentioning
confidence: 99%
“…The biomarkers in the MBDA test reflect the biology of RA and consist of cytokine-related proteins (IL-6, TNF-R1), acute phase reactants (CRP, serum amyloid A), an adhesion molecule (VCAM-1), growth factors (EGF, VEGF-A), matrix metalloproteinases (MMP-1, MMP-3), and adipokines (leptin, resistin). The MBDA score is an integer on a scale of 1 to 100, with disease activity categories of low (< 30), moderate (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) and high (> 44) [10]. Minimally clinically important difference (MCID) for MBDA score is ≥8 [23].…”
Section: Mbda Testingmentioning
confidence: 99%
“…As expected, the median DAS28-ESR, DAS28-CRP, SDAI and CDAI at baseline (2.08, 2.50, 4.1 and 3.7, respectively) were all in the low category. The median (IQR) baseline MBDA score was 31 (18-39) and the median tiMBDA score was 29 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). The heatmap in Fig.…”
Section: Patient Cohortmentioning
confidence: 99%
“…These 12 biomarkers reflect biological pathways involved in the pathogenesis of RA and can be broadly grouped as acute-phase reactants (SAA, CRP), hormones (leptin and resistin), growth factors (VEGF and EGF), adhesion molecules (VCAM1), skeletal-related proteins (YKL-40), matrix metalloproteinases (MMP-1, and cytokine-related proteins (IL-6, TNFR1). The MBDA score has been shown to predict risk for radiographic progression [20]. Therefore, these objective markers may be useful for defining remission on a molecular level and may have potential for predicting sustained remission.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps if defining remission in RA as 0 swollen joints is too difficult, then a biomarker could be a surrogate instead, such as the multibiomarker disease activity score (MBDA) or 14‐3‐3η protein . These measures correlate well with disease activity, and the MBDA may perform better than the CRP level or DAS28 score for radiograph progression , and even if in Simplified Disease Activity Index remission the 14‐3‐3η enzyme‐linked immunosorbent assay levels can predict radiographic progression , they are expensive and have not been tested to determine whether they provide added value to the physician global assessment or the actual SJC. The subspecialty of rheumatology should continue to use the joint assessment with the physical examination to define active RA and remission in RA.…”
Section: Remission Varies Depending On What Definition Is Usedmentioning
confidence: 99%